Exploring indirect communication strategies in the educational organisation: perspective from Jakarta, Indonesia - Eshauqi Fitrayatra; Engkus Kuswarno; Ilham Gemiharto (Jurnal Studi Komunikasi, 2023)
This study investigates the use of indirect communication strategies within an educational institution in Jakarta, Indonesia, focusing on discussing their significance in achieving communication objectives within professional contexts. The primary emphasis is on how these indirect communication strategies are applied to cultivate supportive relationships and create a favourable professional environment within educational settings. The following research questions guide the ethnographic study: 1) How are indirect communication strategies employed in educational organisations? and 2) What factors influence the adoption of these communication strategies? This research utilised four data collection methods: participant observation, in-depth interviews, focus group discussions, and document analysis. Participants in this study included school principals, vice-principals, teachers, support staff, students, and parents from a state primary school in Jakarta, Indonesia. The study's findings reveal that indirect communication strategies are predominantly employed to achieve various communication objectives, such as conveying humour, expressing frustration, delivering implied messages, seeking assistance, and expressing uncertainty. These strategies are deeply rooted in the cultural context, particularly influenced by Betawi culture, which strongly emphasises preserving social harmony and promoting respectful interactions. Several influential factors, including shared cultural values, power dynamics, and age, were identified as elements affecting the adoption of these indirect communication strategies.